Chemical modification and biosynthesis of silk-like polymers. (June 2019) - Katashima, Takuya; Malay, Ali D; Numata, Keiji
Graphical abstract: Highlights: Silk materials attract attention because of their mechanical robustness. The characteristics of silk materials are attributed to their hierarchical structures. Chemical modification and biosynthesis of silk-like polymers are promising approaches. Control of the hierarchical structures is beneficial for the design of novel materials. Abstract : Silk fibers show high toughness, ductility, biocompatibility, and biodegradability due to their high-order structure. Silk materials are not limited to native fibers and also include regenerated silk materials, such as chemically modified silk materials, composite materials, and silk-inspired artificial materials synthesized through chemoenzymatic polymerization. Here, we present the concepts and methodologies associated with the different types of silk-based materials for a wide range of fields including bioengineering and medicine and explore their versatile functionality and physical properties related to their primary and secondary structures. In this review, we will reveal the characteristics of silk materials as well as research prospects for the future.